Pengembangan Media Visual Sebagai Layanan Informasi Yang Efektif Di Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas Bengkulu - Elys Candra Yani; Is Susanti; Siska Jufrise (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
This educational staff research is entitled "Development of Visual Media as an Effective Information Service at the Research and Community Service Institute of the University of Bengkulu." The study aims to improve service delivery so that it becomes more effective and efficient. Effective and efficient service refers to the ability to meet the needs and expectations of service users accurately, promptly, and through the optimal utilization of available resources. To ensure that services are delivered effectively, one highly useful strategy is the use of visual media such as posters. Posters are a form of visual communication that can convey information quickly and attractively, making them an effective medium for disseminating information to service users. Keywords: Visual Media, Public Service, Effectiveness.